Influence of high temperature on microscopic structure of osseous tissue - Młodziejowski, Bronisław; Steć, Janusz (Anthropological Review, 1980)
Fragments of fresh and macerated femoral shafts belonging to 145 persons: of both sexes aged 20 - 40 years served as a material for the present study. A part. of each fragment had been burned in a gas-heated furnace (approx. temperature 1100%C) and subsequently hardened by styrene-benzoiloperoxide-polystyrene system. Slices of bone were prepared for microscopic examination from both burned and unburned fragments. It has been found that a process of burning does not change microscopic properties of bone to an extent precluding observation and interpretation of important details. When macerated dry bone is burned tissue is less damaged than in a case of fresh, damp bone rapidly drying up during cremation. Degree of shrinking caused by cremation is estimated at about 10% on grounds of average: dimension of Haversian channels.